Adult-onset Krabbe disease presenting with progressive myoclonic epilepsy and asymmetric occipital lesions: A case report - Wang, Yu; Wang, Su-yue; Li, Kai; Zhu, Yu-long; Xia, Kun; Sun, Dan-dan; Ai, Wen-long; Fu, Xiao-ming; Ye, Qun-rong; Li, Jun; Chen, Huai-zhen (Frontiers in Neurology, 2022)
Krabbe disease (KD), also known as globoid cell leukodystrophy, is a rare autosomal recessive condition caused by mutations in the galactocerebrosidase (GALC) gene. KD is more common in infants and young children, but it is also described in adults. We reported the case of an adult-onset KD presenting with progressive myoclonic epilepsy (PME) and cortical lesions mimicking mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome. The whole exome sequencing identified a pathogenic homozygous missense mutation of the GALC gene. Her parents were heterozygous for the mutation. The clinical, electrophysiological and radiological data of the patient were retrospectively analyzed. She was a 24-year-old woman presenting with generalized seizures, progressive cognitive decline, psychiatric symptoms, gait ataxia and action-induced myoclonus. The brain magnetic resonance imaging (MRI) revealed a right occipital cortical ribbon sign without any other damage. This single case expands the clinical phenotypes of adult-onset KD, suggesting that abnormal cortical signals can be indicative of an early stage of the disease.